Bleaching process of Kekabu (Ceiba spp) using soda AQ pulp / Aishah Md Yunos, Norazira Mohd Sayuti and Nurnazirah Mahamad - Md Yunos, Aishah; Mohd Sayuti, Norazira; Mahamad, Nurnazirah (2008)
The research is about the bleaching process from Soda AQ Pulping. Kekabu are used as raw material. NaOH are used as chemical active material and in this experiment, the amount of NaOH is 20%. The chemical additive that use is AQ in amount about 0.1%. bleaching process involve two sequence, DEDEH and DEHED and the process done by using Water Bath. The paper testing are followed by ISO Standard to determine the physical properties of paper. While between the bleaching sequences, DEHED has better paper properties than DEDEH, but for brightness test, DEDEH is better than DEHED. Generally, unbleached pulps have better result than bleaching pulp. This is because during bleaching by using chlorine dioxide besides remove the remaining lignin, it also attacked cellulose, thereby will reducing pulps strength.